Analisis Faktor Risiko Penyakit Tidak Menular pada Remaja di Daerah Perkotaan: Studi di SMA Muhammadiyah 2 Jakarta - Wilda Yunieswati; Anisa Sekar Widhi; Rosyanne Kushargina; Almira Nuraelah (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2026)
All age groups, including children, teenagers, adults, and the elderly, are at risk for non-communicable diseases (NCDs). One of the places where non-communicable illnesses may become more prevalent is urban areas. Changes in urban lifestyles may contribute to the rising prevalence of non-communicable illnesses. Basic research is necessary to understand the picture of infectious illnesses and associated risk factors, particularly in urban areas, since the growing number of NCD cases is predicted to raise the cost on the government and society. A cross-sectional research approach was employed in this investigation. The research was carried out at SMA Muhammadiyah 2 Jakarta. Eighty-one people were chosen as samples using simple random selection. Body weight, height, blood sugar, and uric acid levels measured directly are examples of primary data. In the meanwhile, questionnaires and interview techniques were used to gather information on respondent characteristics, medical history, and risk factors. The majority of responders reported normal uric acid levels (95.1%) and normal random blood sugar levels (93.8%). Nutritional status, breakfast routines, eating habits, smoking habits, personal and family medical histories, and physical activity are risk factors for non-communicable illnesses. Type 2 diabetes mellitus and uric acid were the non-communicable illnesses examined in this study; the chi-square test revealed no significant correlation between infectious diseases and their risk variables in the participants.